Sustainable Removal of Methyl Orange from Wastewater Using Cyperus rotundus : A Low-cost Natural Adsorbent - Ahmed , Ahmed A.; Mustafa, Rawezh M.; Saleh, Dunya I.; Swara, Bahra J.; Al-Wakeel, Ali; Abdul, Dastan S. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2026)
Synthetic dyes found in wastewater create substantial environmental hazards and health risks, which require effective and sustainable wastewater treatment methods. This study investigates the use of Cyperus Rotundus as a natural adsorbent to remove methyl orange in aqueous solutions under a batch system. A total of 71 experimental runs were conducted to examine the effects of initial dye concentration (5–100 ppm), pH (3–11), contact time (10–90 min), and temperature (25–45°C) on the adsorption process. The maximum removal efficiency of 97% was obtained at a dye concentration of 10 ppm, pH of 4, and contact time of 90. Isotherm analysis revealed that the Langmuir model can provide the best fit with a maximum adsorption capacity of 2.25 mg/g, and a coefficient of determination (R2 = 0.657) while kinetic data followed the pseudo-second-order model indicating that chemisorption is the dominant mechanism (R2 > 0.95). Thermodynamic analysis proved that this adsorption is both spontaneous (with a standard Gibbs free energy change ranging from ΔGo = - 4.76 to -5.69 kJ/mol) and endothermic (enthalpy change ΔH° = 9.10 kJ/mol). Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) were used to confirm the presence of dye adsorbent interactions by testing structural and functional changes of the groups that occurred after adsorption. The results show that Cyperus Rotundus is a low-cost biosorbent in methyl orange removal and can serve as a sustainable wastewater treatment material.